Student Participation: Issues for the Governance of Higher Education - Albertina Palma; Joaquim Mourato; João Vinagre; Fernando Almeida; Ana Maria Pessoa (Societies, 2023)
The paper reports findings of a research project aimed at developing insight into student participation in the governance of higher education institutions. The project was carried out in two institutions in Portugal, analyzing numbers and forms of participation, identifying facilitators and constraints to participation, and analyzing the students’ perceptions of their own participation. The study was carried out in the context of the European purpose of creating a cohesive European Higher Education Area (EHEA), and in light of theoretical perspectives of the sociology of public action. The concept of participation put forward by the Council of Europe in 2003 was mobilized in the sense that true participation involves making a difference in decision-making. The research objectives required both quantitative and qualitative data collection; therefore, a mixed-methods approach was adopted, including document analysis, interviews, and a questionnaire. The cross-analysis of the data collected enabled the researchers to characterize the participation of students in formal governing bodies and in other institutional contexts, identify facilitators and constraints to participation resulting either from the legal framework, the institutional culture, or personal contexts, and simultaneously capture individual perceptions of participation on the part of the students. The results enabled the authors to make a set of recommendations for political action both at national and institutional levels.